Design of Packaging Materials Based on Polylactide and Wood Filler - R. Safin, R.; A. Talipova, G.; R. Galyavetdinov, N. (International Journal of Engineering and Technology, 2018)
Packaging is one of the primary factors that influence the consumer’s decision to purchase a product. Competent packaging design makes it possible to distinguish the product from competitors’ products, to attract the attention of the target audience, to raise the mood of the buyer,and to cause trust in the brand. Currently, packaging materials from various types of polymers are a popular and widely used type of packaging, but at the same time such materials pose a serious burden on the environment. In this regard, the development of new types of biodegradable materials for the packaging industry is relevant. The article considers the possibility of using a composite material for packing based on polylactide (PLA) and filler from crushed biomass waste. It was established that PLA packaging with the addition of 50% wood filler will provide high strength characteristics with the ability to create container packaging, as well as provide a high rate of biodegradation of used packaging, thereby reducing the environmental burden on the environment. At the same time, the cost of such a composite will be comparable to the cost of synthetic polymers obtained from non-renewable hydrocarbon raw materials.